Pengaruh Naungan Tegakan Pohon Terhadap Pertumbuhan dan Produktivitas Beberapa Tanaman Sayuran Indigenous - Rina Ekawati; Anas D. Susila; Juang G. Kartika (Jurnal Hortikultura Indonesia, 2010)
ABSTRACTThe objectives of this research was to study the effect of shade on growth and productivity of several indigenous vegetables. The research was conducted at Vegetable Garden, University Farm IPB, Darmaga from February until June 2009. This research was arranged in a Randomized Completely Block Design, 1 factor with 2 treatments, shading (N1) and no shading (N0). Result of the research showed that shading increased plant height, length of branch, leaf length and width of Daun Ginseng (Talinum triangulare); leaf diameter, leaf length and width, petiole length of Sambung Nyawa (Gynura procumbens); leaf length and width of Katuk ( Sauropus androgynus); leaf number of Kenikir (Cosmos caudatus), stem diameter of Kemangi (Ocimum americanum); plant height, length of branch, number of branch, leaf length and width of Pohpohan (Pilea trinervia). Shading also increased total fresh and dry weight/plant of Daun Ginseng; and total fresh/plant of Sambung Nyawa and Pohpohan plants. Productivity of Daun Ginseng and Pohpohan at shade field was better than at open field. Daun Ginseng, Sambung Nyawa, Kenikir, Kemangi and Pohpohan plants prefered growing at low light intensity (shade plants).Key words: indigenous vegetable, shading, growth, productivity